2018
DOI: 10.2147/tcrm.s179334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of the Cervista<sup>&reg;</sup>&nbsp;high-risk human papillomavirus test in Chinese women from Fujian province: a cross-sectional study

Abstract: PurposeTo estimate the high-risk human papillomavirus (HR-HPV) prevalence in a hospital-based population using the Cervista® and to determine the clinical value and significance of Cervista for cervical cancer screening in Fujian Province, China.Patients and methodsIn a hospital-based population, a total of 10,771 women from the Fujian Province were screened for cervical cancer and precancerous lesions using the thinprep cytologic test (TCT) and/or the Cervista. Women with HR-HPV infection and/or abnormal TCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…It is well known that HPV‐16 and HPV‐18 are the predominant high‐risk types found in cervical cancer worldwide, whereas the prevalence of the other high‐risk HPV types may show geographical and regional variation. According to our data, the most common types of HPV in Shenzhen, a city in the southeast of China with a population of 18 million, were HPV‐52, 53, 16, 58, and 51, whereas HPV‐35, 45, 73, and 82 were consistently the least frequently detected (Figure 2), which were consistent with the data from single‐center or multicenter studies in China 30,32 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is well known that HPV‐16 and HPV‐18 are the predominant high‐risk types found in cervical cancer worldwide, whereas the prevalence of the other high‐risk HPV types may show geographical and regional variation. According to our data, the most common types of HPV in Shenzhen, a city in the southeast of China with a population of 18 million, were HPV‐52, 53, 16, 58, and 51, whereas HPV‐35, 45, 73, and 82 were consistently the least frequently detected (Figure 2), which were consistent with the data from single‐center or multicenter studies in China 30,32 …”
Section: Discussionsupporting
confidence: 90%
“…According to our data, the most common types of HPV in Shenzhen, a city in the southeast of China with a population of 18 million, were HPV-52, 53, 16, 58, and 51, whereas HPV-35, 45, 73, and 82 were consistently the least frequently detected (Figure 2), which were consistent with the data from single-center or multicenter studies in China. 30,32 In this cohort of patients, the highest HPV prevalence (13.52%) was found in women older than 50 years of age, which was discordant from the results reported in many studies, as the prevalence of HPV infection was higher at younger age and decreased with age. Reasons for such conflicting results remain unclear but the most possible explanation could be the opportunistic screening program in which women tend to participate at a later age.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The detailed experimental procedures of the Cervista ® HR-HPV assay can be found online ( https://www.hologic.com/sites/default/files/package-insert/15-3100_105_01.pdf ). Our study and previous studies [ 21 , 22 ] have demonstrated that the Cervista ® HR-HPV assay is an effective HR-HPV detection method.…”
Section: Methodssupporting
confidence: 74%